Incidence and risk factors for postoperative delirium after major head and neck cancer surgery. Issue 7 (July 2016) - Booka, Eisuke; Kamijo, Tomoyuki; Matsumoto, Teruaki; Takeuchi, Mari; Kitani, Takashi; Nagaoka, Masato; Imai, Atsushi; Iida, Yoshiyuki; Shimada, Ayako; Takebayashi, Katsushi; Niihara, Masahiro; Mori, Keita; et al.
Abstract: Background: Postoperative delirium is a common and serious complication after extensive surgery. This study aimed to investigate the incidence and risk factors for postoperative delirium after major head and neck cancer surgery. Methods: A retrospective analysis was performed for 293 patients who underwent major head and neck cancer surgery lasting >6 h at our institution between January 2012 and November 2015. All data were assessed by two psychiatrists. Univariate and multivariate analyses were performed. Results: Postoperative delirium developed in 50 (17.1%) patients; most cases (84.0%) of postoperative delirium were observed between postoperative day (POD) 1 and POD 3. Multivariate analysis revealed that an age >70 years was the significant risk factor for postoperative delirium incidence after major head and neck cancer surgery; the multivariate hazard ratio was 3.935 (95% confidence interval 1.873–8.265, p  < 0.001). Conclusions: Most cases of postoperative delirium after major head and neck cancer surgery were observed between POD 1 and POD 3, and a multivariate analysis revealed that an age >70 years was a significant risk factor for postoperative delirium incidence. Clinicians should pay particular attention to the possibility of delirium incidence during the first 3 days after surgery for patients aged >70 years.